Improving Image Quality in Old Photos Using Histogram Equalization and Intensity Adjustment Methods - fadillah, Ok Muhammad Zikri; Winata, Muhammad Agung; Fachreza, Fikri; Hafiz HS, Fauzan; Saprin, Muhammad (Cattleya Darmaya Fortuna, 2025)
Old photos often experience a decline in image quality due to age and the limitations of previous camera technology. This makes important visual details difficult to observe. This research aims to improve the image quality of old photos using histogram equalization and intensity adjustment methods with the MATLAB application. This method manipulates the image intensity distribution to obtain more optimal contrast and brightness. The test results show a significant increase in visual detail, histogram distribution, and image contrast values ​​compared to the original photo. However, this method still has limitations in reducing noise so further research is needed for better results.